Gender and tourism consumption in Brazil: analysis of family budgets in the perspective of intersectionality - Gabrielli, Cassiana Panissa; Medaglia, Juliana; Santos, Glauber Eduardo de Oliveira (Anais Brasileiros de Estudos Turísticos, 2023)
This article aims to analyze the relationship between gender and tourism consumption in Brazil from the perspective of intersectionality with sociodemographic characteristics such as race, income and household condition (urban/rural). This work is embedded in the growing debate about social agendas in the tourist context, linked to the lack of statistical data and information that allow stratified analyzes by social markers. The research analyzes data from the IBGE’s Household Budget Survey (2017-2018), using descriptive statistics techniques, in addition to parametric tests and multivariate modeling. The modeling of tourist consumption made it possible to examine the conditional effects of each sociodemographic variable, seeking to describe the relationships between the explanatory variables and tourist consumption. Descriptive results indicate that households headed by women tend to consume less tourism than those headed by men. However, the analysis of conditional effects suggests that this difference is due to income inequality, and not directly to the gender difference. In this way, the intersectional analysis made it possible to clarify the structure behind the observable gender inequality in tourist consumption, pointing to income as a transmission and perpetuation mechanism of the lower access of women to travel.